The importance of health education for the control of Visceral Leishmaniasis - Célia Loverdi de Lima Stringheta, Regina; Maria Savoya da Silva, Valéria; Bertequni Nagata, Walter; Alessandra Mira Luz Requena, Keuryn; Mara Tomiko Suto, Tania; Aparecida Colebrusco Rodas, Lilian; da Silveira Neto, Luiz; Fernando Ribeiro Manhoso, Fábio; Denise Saraiva Bresciani, Katia (Seven Editora, 2023)
This study aimed to highlight the importance of health education for the control of VL (Visceral Leishmaniasis). They used the platforms Google Scholar, Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), and studies distributed in the databases PubMed and Capes Journals with the keywords: Visceral Leishmaniasis, Health Education, Public Health and Vectors, in addition to free terms related to the objective, such as environmental education and sandflies. The inclusion criteria were language (Portuguese and English) and availability (full text). The bibliographic references contained in the works found were also used in this review, as well as the official publications of the Brazilian government, such as the Manual of Surveillance and Control of visceral leishmaniasis. It is concluded that a large part of the population does not know the vector, proliferation, and methods of control of VL, for this reason, implementing educational actions of health education is essential to increase the level of knowledge through information related to the disease, and thus also reduce other diseases of similar epidemiological characteristics. DOI: https://doi.org/10.56238/devopinterscie-208